Factors and Mechanisms Influencing Consumers’ Willingness to Participate in Food Safety Social Co-governance: An Empirical Study from China - Zhang, Chunsheng; Ji, Mingxin; Deng, Zhaoyan; Wu, Di (Applied mathematics and nonlinear sciences, 2024)
Food safety governance and its performance improvement are inseparable from the cooperation of multiple subjects. The extensive participation of consumers is not only a powerful supplement to the deficiency of supervision resources but also an intrinsic request for seeking both temporary and permanent solutions to food safety problems. To ascertain the factors and mechanisms that influence consumers’ participation willingness of food safety social co-governance, an integrated conceptual model was constructed based on the Theory of Planned Behavior (TPB) and Benefit-Risk Analysis (BRA). 664 valid questionnaires collected in China were used to verify the hypotheses with the application of the Structural Equation Model (SEM). The results showed that behavior attitude, subjective norm, and perceived behavior control significantly impacted consumers’ participation willingness, and the influence strength was in the sequence of perceived behavior control, behavior attitude, and subjective norm. Perceived risk and participation willingness showed a strong negative relationship. Besides that, perceived risk also played a partial mediation role in predicting behavior attitudes toward consumers’ participation willingness. According to the conclusions, a series of policy suggestions were also proposed to help improve consumers’ participation willingness.